2004
DOI: 10.1152/ajpendo.00575.2003
|View full text |Cite
|
Sign up to set email alerts
|

Defect in glucokinase translocation in Zucker diabetic fatty rats

Abstract: Hepatic glucose fluxes and intracellular movement of glucokinase (GK) in response to increased plasma glucose and insulin were examined in 10-wk-old, 6-h-fasted, conscious Zucker diabetic fatty (ZDF) rats and lean littermates. Under basal conditions, plasma glucose (mmol/l) and glucose turnover rate (GTR; mol ⅐ kg Ϫ1 ⅐ min Ϫ1 ) were slightly higher in ZDF (8.4 Ϯ 0.3 and 53 Ϯ 7, respectively) than in lean rats (6.2 Ϯ 0.2 and 45 Ϯ 4, respectively), whereas plasma insulin (pmol/l) was higher in ZDF (1,800 Ϯ 350) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 66 publications
5
51
1
Order By: Relevance
“…augmented by 38% when compared with that of the nondiabetic animals, strongly suggest that renal gluconeogenesis may contribute crucially to the hyperglycemia and the elevated systemic glucose production observed in these animals (49). Among the factors that potentially are involved in the probably multifactorial long-term stimulation of renal gluconeogenesis that we observed, our results suggest that both glucocorticoids and cAMP might play a substantial role by augmenting the expression of key gluconeogenic genes…”
Section: Resultssupporting
confidence: 53%
“…augmented by 38% when compared with that of the nondiabetic animals, strongly suggest that renal gluconeogenesis may contribute crucially to the hyperglycemia and the elevated systemic glucose production observed in these animals (49). Among the factors that potentially are involved in the probably multifactorial long-term stimulation of renal gluconeogenesis that we observed, our results suggest that both glucocorticoids and cAMP might play a substantial role by augmenting the expression of key gluconeogenic genes…”
Section: Resultssupporting
confidence: 53%
“…Previous studies have shown that glucose-induced translocation of glucokinase from the nucleus to the cytoplasm is impaired in models of insulin resistance and diabetes such as the Goto-Kakizaki, OLETF (41), and Zucker diabetic fatty rats (20,21). However, the underlying mechanisms have not been determined.…”
Section: Discussionmentioning
confidence: 98%
“…Defects in glucokinase translocation have been reported in animal models of Type 2 diabetes, including the Goto-Kakizaki rat and the Otsuka Long Evans Tokushima Fatty (OLETF) rat (41) and the Zucker diabetic fatty rat (20,21). The Zucker diabetic rat had impaired glucokinase translocation during a glucose and insulin infusion (21).…”
mentioning
confidence: 99%
“…Functional GK activity in the liver is also allosterically regulated by its interaction with a 68-kDa GK regulatory protein (GKRP), which binds to GK and inhibits the enzyme by a decrease in the apparent enzyme affinity for glucose (58). Studies using both cultured hepatocytes (2,10,32) and performed in vivo (13,22,23) demonstrated that GK is sequestered in the nucleus by GKRP under conditions of low glucose and insulin concentrations and that in response to a rise in glucose and/or insulin concentration, GK is dissociated from GKRP and is rapidly transported to the cytoplasm. It is likely, therefore, that stimulation of GK translocation by glucose plays an important physiological role in glucose effectiveness to stimulate its own uptake and inhibit its own production by the liver in normal subjects.…”
mentioning
confidence: 99%